Leo Tolstoy - Bayley, John 1925-2015 (Northcote House Publishers, 1997)
A modern study by a distinguished and elegant critic of Tolstoy's most significant achievement in writing
Keywords: Tolstoy, Leo / graf / 1828-1910 / Criticism and interpretation; Tolstoj, Lev Nikolaevič -- 1828-1910; Literatur